Application of dynamic programming for students financial planning / Najihah Mohd Hasnan ... [et al.] - Mohd Hasnan, Najihah; Yahya Haris, Afiqah Nornajwa Huda; Mohd Hisham, Siti Noor Ameera; Wan Abdul Aziz, Rossidah; Wan Abdul Aziz, Wan Noor Hayatie (Universiti Teknologi MARA, Negeri Sembilan, 2023)
According to Walker (2005), financial planning means a process of framing financial policies in relation to procurement, investment and administration of funds. Having a proper way of handling finances has always been a norm to society because financial planning is not just about handling money concurrently but includes predicting future income, assets values and withdrawal plans (Voigt & Benson, 2022). Every person's goals vary from each other following personal objectives and purposes meaning that each needs a suitable setting to satisfy each need. Malaysian Reserve reveals that 50% of Malaysian having difficulties in raising RM1,000 during emergencies and only 40% elders are ready for retirement. To only start managing finances during this age will be too late thus this study proposed a financial planning for students. It is to support Malaysians in ensuring a better outcome by exposing young people to a well-behaved plan of managing finances.